Shared Detection Of Cyberattacks On VoIP Exchanges - Jezek, Jiri (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2021)
In the last decade, security in Voice over IP raises on importance. This article focuseson shared defence systems in VoIP, summarizes the existing work related to this topic. In standardsystems with basic security, it is common to monitor attacks and prevent them with certain countermeasures.A problem occurs when multiple PBXs are connected to one network because the individualPBXs do not know that other network entities are attacked. It can lead to the attack spreadingto other devices connected to one network and significantly slowing the whole network. This paperproposes a solution focused on sharing information about an attacker with other network entities byusing method MESSAGE from SIP protocol.